Strategi Akomodasi Komunikasi Mahasiswa Asal Nigeria (Studi Fenomenologi pada Mahasiswa Program Sarjana Asal Nigeria dalam Melakukan Adaptasi Budaya di Kampus) - Aghnia Brenda Nadhira; Sri Hastjarjo (Universitas Sebelas Maret (UNS), 2025)
Universities in Indonesia are now actively and ambitiously opening up internationalization opportunities for foreign students to have the opportunity to continue their higher education in Indonesia. This is also done by Sebelas Maret University, marked by the presence of Nigerian students in the Bachelor's program.The arrival of foreign students requires adaptation. This study uses a phenomenological approach to explore the in-depth experiences of Nigerian students in navigating the challenges and barriers of intercultural communication in the campus environment. This study focuses on the theory of accommodation strategies presented by Morrisan & Corry (2009), consisting of three options, namely: convergence, divergence, and excessive accommodation which are part of their adaptation. Using qualitative methods with data collection techniques in the form of in-depth interviews and documentation. The subjects of the study were Nigerian students who had gone through a critical period, namely at least in the fifth semester of the undergraduate education program or who had been students of Sebelas Maret University for two years. The results of the study showed that there was the use of convergence and divergence strategies. And all informants were at the accommodation stage in cultural adaptation.